Performance and Emission Characteristics of Homogeneous Charge Compression Ignition Engine with Different Bio Diesel Fuels - Moulali, P; Prasad, T H; Prasad, B D (International Journal of Engineering and Technology, 2018)
In this paper the emission characteristics and performance of various bio diesel fuels (Tyre pyrolysis oil (TPO), Micro algae oil and Pig animal fat oil) were experimented. A single cylinder, water cooled diesel engine was modified in to homogeneous charge compression ignition engine (HCCI) with adopted port fuel injection (PFI) technique. The effects of air fuel ratio, intake temperature, injection pressure and EGR rate exhaust emissions were explained in a broad manner. The analysis of the exhaust emissions are integrated to oxides of Nitrogen (NOx), Carbon Monoxide (CO), unburned hydro carbons (UHC), smoke and soot. The performance analysis was also included on specific fuel consumption and break thermal efficiency. The basic requirements for HCCI engine is the homogeneous mixture preparation of air and fuel. This mixture formation was done by adopting port fuel injection technique and external devices were also used for bio diesel vaporization and mixture preparation. The combustion processes were measured with different EGR system.Â  The experimental results of different bio diesel fuels with HCCI engine mode were recorded and evaluated. A small increase in CO and HC emissions were observed with increasing bio diesel content due to slow evaporation rate of bio diesel. A significant reduction in NOx emission was also observed with respect to difference in bio diesel blends. Micro algae oil was found more stable compared with other bio diesel fuels due to the property of fuel vaporization and low heat releasing.